Rancangan Sistem Monitor Flight Plan di Bandar Udara Temindung Samarinda - Sabur, Fatmawati; Pangestu, Sandhy (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Transmission of filght plan from Samarinda Temindung airport to Balikpapan Sepinggan airport has been sometimes failed because of various things such as breaking off the communication way or another supporting facility failure such as VSAT. So if flight plan’s data from Samarinda BO to Balikpapan BO is not sent, then Samarinda BO will resend that filght plan. The objective of this design was to make an application which is able to monitor flight plan at tower of Samarinda Temindung airport and to invent a device which could be used to send notification to the technician if there any trouble on AFTN. The method of this design used microcontroller component, GSM modul, and Microsoft Visual Studio 2013 application. The aim of this design had shown the simulation of that device would be able to give a description about flight plan transmission monitoring system which transmit and receive into Samarinda Temindung airport.